2015
DOI: 10.3171/2015.4.peds1545
|View full text |Cite
|
Sign up to set email alerts
|

Linear nondisplaced skull fractures in children: who should be observed or admitted?

Abstract: OBJECT In this study the authors reviewed clinical management and outcomes in a large series of children with isolated linear nondisplaced skull fractures (NDSFs). Factors associated with hospitalization of these patients and costs of management were also reviewed. METHODS After institutional review board approval, the authors retrospectively reviewed clinical records and imaging studies for patients between the ages of 0 and 16 years who were evaluated for NDSFs at a single children’s hospital between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 17 publications
2
22
0
1
Order By: Relevance
“…Further evidence that a higher level of care may not be warranted comes from large studies that specifically examined transfers of pediatric ILSF to Level 1 Pediatric Trauma Centers [6, 12, 19, 20]. Similar to these studies, the vast majority of our patients were transfers from outside hospitals.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Further evidence that a higher level of care may not be warranted comes from large studies that specifically examined transfers of pediatric ILSF to Level 1 Pediatric Trauma Centers [6, 12, 19, 20]. Similar to these studies, the vast majority of our patients were transfers from outside hospitals.…”
Section: Discussionsupporting
confidence: 58%
“…Our data answers a specific question that previous papers have alluded to, but not emphasized, in their results [6, 7, 10, 12, 14, 15]. To briefly summarize, Arrey et al [6] determined that there was no need to hospitalize 326 patients with ILSF with a median age of 19 months unless there was a pending nonaccidental trauma workup.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, it is controversial whether performing follow-ups of these cases by hospitalizing them is cost-effective [8][9][10]. It has been reported that the number of cases having isolated fractures that require neurosurgical intervention is very low and mortality is <0.1% [7,10].…”
Section: Discussionmentioning
confidence: 99%